EFL Students’ Speaking Anxiety During Presentation Performance at Language Center Kampung Inggris Pare - Zesshreena Hatiza; Ahmad Heki Sujiatmoko (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Presentation is not easy to do. This is because many students experience anxiety during presentation performance. This research aimed to investigate various types of EFL students' speaking anxiety and to know the possible factors that influence EFL students' speaking anxiety in Language Center during presentation performance. The researcher used quantitative research with a survey design. A questionnaire was used to collect the data. The participants were 50 students at the Language Center Kampung Inggris Pare who took the intensive program for one month in class B. This study found that there were three types of speaking anxiety related to presentation performance in EFL students at the language center: communication apprehension, test anxiety, and fear of negative evaluation. In addition, internal and external factors influence speaking anxiety, including shyness, embarrassment, lack of self-confidence, fear of making mistakes, motivation, limited vocabulary, lack of preparation, grammatical errors, and friends/classmates. It is recommended that teachers pay attention to the students’ anxiety in doing presentations because controlling the anxiety will make the presentation successful